SINKRONISASI PASAL 1868 KUHP PERDATA DALAM MENUNJANG TERSELENGGARANYA KONSEP CYBER NOTARY DI INDONESIA - Apriandy Iskandar Dalimunthe,; Achmad Fitrian,; Mardi Candra, (Journal of Innovation Research and Knowledge, 2023)
The implementation of cyber notary in Indonesia raises legal phenomena. On the one hand, cyber notary enhances the capabilities of Notaries in accordance with current technological developments. On the other hand, cyber notary creates an unsynchronization between traditional Notary tasks and digital Notary tasks. The purpose of writing is to synchronize the implementation of the tasks of the Notary according to the Law and the Civil Code, and the implementation of the tasks of the Notary according to the ITE Law. The research method used by the author is Normative Juridical supported by empirical research. The results of the study and the conclusion that the application of cyber notary in Indonesia raises doubts for the Notary regarding the saving of the minutes of the deed, must be stored manually or electronically, in line with the lack of legal basis governing the mechanism for the storage of the minutes of the deed. The conclusion is cyber notary in Indonesia should not be fully implemented and there needs to be some consideration because the legal system in Indonesia with the legal system in other countries is much different.